Cross section measurement of t-channel single top quark production in pp collisions at root s=13 TeV - Sirunyan, A. M. (2017)
The cross section for the production of single top quarks in the t channel is measured in proton- proton collisions at 13TeV with the CMS detector at the LHC. The analyzed data correspond to an integrated luminosity of 2.2fb(-1). The event selection requires one muon and two jets where one of the jets is identified as originating from a bottom quark. Several kinematic variables are then combined into a multivariate discriminator to distinguish signal from background events. A fit to the distribution of the discriminating variable yields a total cross section of 238 +/- 13 (stat)+/- 29(syst) pband a ratio of top quark and top antiquark production of Rt-ch.= 1.81 +/- 0.18 (stat)+/- 0.15(syst). From the total cross section the absolute value of the CKM matrix element Vtbis calculated to be 1.05 +/- 0.07 (exp)+/- 0.02(theo). All results are in agreement with the standard model predictions. (C) 2017 The Author(s). Published by Elsevier B.V.